PENNGEMBANGAN SISTEM INFORMASI AKADEMIK FAKULTAS TEKNIK UNIVERSITAS TANJUNGPURA - Noviandi, Fedi Rahadi (Jurusan Informatika Universitas Tanjungpura, 2013)
Academic Information Systems or betterknown as SIAKAD, is a system thatbuilt for the fulfillment of the data andinformationneeds on the academic colleges. SIAKAD that built at the Department of ElectricalEngineering Faculty of EngineeringUniversity is a kind ofintegration and development atthe Department of ElectricalEngineering SIAKAD which was built intwo platforms, desktop-based for FacultyOperator and web-based that runin the EngineeringFaculty intranet for Students. Furtherdevelopment on SIAKAD to facilitatetechniques users in processing and accessdata online, through Internet connectednetworks.Literaturestudies, datacollection, system requirementsanalysis, system design, implementationand testing and the analysis of the testresults, are steps in this research. Thesesteps resulted a SIAKAD of ElectricalEngineering Department, where this systemgrant permissions on four different types ofusers, called Faculty Operator, AcademicOperator, Lecturers and Students. In orderto design this system, researcher used adiagram methodical approach that isdivided into three kind of diagram modelsuch as, Data Flow Diagrams (DFD) todescribe the flow of data on a system thatconsists of two main parts of the systemdata input and data flow analysissystem, flowchart diagram to describesystem used and Entity Relationshipdiagram (ERD) to explain the relationshipbetween the data in the database based onthe data base objects that haverelationships in between. By analyzing theneeds of the academic system, a web-basedAcademic Information System is able tocombine the features of two previoussystems of different platforms thatacademic communication and dataexchange between operators, lecturers,students and academics can be carried outsmoothly. web-based siakad can be used bystudents, faculty, and academic operators,with each having access rights and differentfeatures, so operating in the communicationand exchange of academic data runsmoothly.